Guidance of Unmanned Surface Vehicle Fleet Using Genetic Algorithm-Based Approach - Dvořák, Miroslav; Doležel, Petr; Štursa, Dominik; Chouai, Mohamed (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
In this contribution, we provide an approach to guidance of a fleet of unmanned surface vehicles. While the vehicles are themselves completely autonomous in their operational locomotion and obstacle avoidance, the task assignment for each vehicle is provided by a global planning process, based on the genetic algorithm. Various possibilities to the genetic algorithm are proposed and tested using a fleet of six vehicles dealing with a complex task.
Navádění flotily bezpilotních pozemních vozidel pomocí přístupu založeného na genetickém algoritmu
Keywords: fleet of unmanned vehicles; genetic algorithm; global planning; flotila bezpilotních vozidel; genetický algoritmus; globální plánování